SURVEY OF NURSING STUDENTS KNOWLEDGE ABOUT THE USE OF 3S REFERENCE (SDKI, SLKI, SIKI) ON NURSING CARE DOCUMENTATION - Mukhtar, Musdalifah; Risnah, Risnah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: The application of the Indonesian Nursing Diagnosis Standards (SDKI), the Indonesian Nursing Intervention Standards (SIKI) and the Indonesian Nursing Outcomes Standards (SLKI) are very important for nurses to know in carrying out nursing care practices in all health care settings. Nursing diagnoses are part of the stages of the nursing process, currently the SDKI is used as a benchmark and guide in establishing nursing diagnoses in order to provide effective and safe nursing care.Method: This study uses a quantitative design with descriptive analysis by measuring the frequency distribution. using accidental sampling which refers to the inclusion criteria and exclusion criteria set by the researcher. The research will be conducted using a Google Form and distributed to nursing students at nursing education institutions in the AIPNI Regional XII area.Results: The characteristics of the majority of research respondents are in the age range of 17-25 years (67.4%), the dominant gender is female (87.2%), Muslim (74.5%), and the origin of the location of the institution is mostly from South Sulawesi (33.5%). The level of knowledge of respondents was in the low category as many as 234 respondents (58.5%), enough category 158 respondents (39.5%), and good category as many as 8 respondents (2%).Conclusions: The level of knowledge majority in the low category, so we need to increase the knowledge of nursing students about the use of SDKI, SLKI, and SIKI references in nursing care documentation, for example through socialization and training on the use of 3S.